Development of a Transcatheter Tricuspid Valve Prosthesis Through Steps of Iterative Optimization and Finite Element Analysis. Issue 10 (17th September 2015) - Pott, Desiree; Kütting, Maximilian; Zhong, Zhaoyang; Amerini, Andrea; Spillner, Jan; Autschbach, Rüdiger; Steinseifer, Ulrich
Abstract The development of a transcatheter tricuspid valve prosthesis for the treatment of tricuspid regurgitation (TR) is presented. The design process involves an iterative development method based on computed tomography data and different steps of finite element analysis (FEA). The enhanced design consists of two self‐expandable stents, one is placed inside the superior vena cava (SVC) for primary device anchoring, the second lies inside the tricuspid valve annulus (TVA). Both stents are connected by flexible connecting struts (CS) to anchor the TVA‐stent in the orthotopic position. The iterative development method includes the expansion and crimping of the stents and CS with FEA. Leaflet performance and leaflet–stent interaction were studied by applying the physiologic pressure cycle of the right heart onto the leaflet surfaces. A previously implemented nitinol material model and a new porcine pericardium material model derived from uniaxial tensile tests were used. Maximum strains/stresses were approx. 6.8% for the nitinol parts and 2.9 MPa for the leaflets. Stent displacement because of leaflet movement was ≤1.8 mm at the commissures and the coaptation height was 1.6–3 mm. This led to an overall good performance of the prosthesis. An anatomic study showed a good anatomic fit of the device inside the human right heart.